Antipyretic Activity of Ethanol Extract from Beligo (Benincasa hispida (Thunb.) Cogn.) Fruit Flesh in Wistar Albino Rats (Rattus norvegicus) - Nur Alim; Rusman Hasanuddin; Jasmiadi Jasmiadi; Musdalifah Musdalifah; A. Ihdinal Hagg; Nur Linda (Sam Ratulangi University, 2023)
The people of South Sulawesi employ beligo as a plant with fever-reducing properties. The utilized part is the flesh of its fruit. The beligo fruit contains fatty acids, flavonoids, phenolics, and steroids that hold promise as antipyretic agents. The study aimed to determine the antipyretic activity of ethanolic extract from beligo fruit flesh on male Wistar rats induced with peptone solution. The research method encompassed maceration extraction using 70% ethanol solvent and antipyretic activity testing using 15 male Wistar rats divided into five treatment groups. Group I served as the negative control and received SODIUM-CMC 1%, groups II, III, and IV received ethanolic extract of beligo fruit flesh at doses of 250 mg/kg BW, 500 mg/kg BW, and 750 mg/kg BW respectively, and group V, the positive control, received paracetamol tablets. Measurements of initial temperature, temperature after induction, and temperature after treatment were taken at 30-minute intervals for 180 minutes. Data were statistically analyzed using a Completely Randomized Design (CRD) and Duncan test. The research findings revealed a fever reduction percentage of 1,57% for group I, 4,03% for group II, 4,28% for group III, 4,45% for group IV, and 5,25% for group V. Data analysis indicated that ethanolic extract of beligo fruit flesh at doses of 250 mg/kg BW, 500 mg/kg BW, and 750 mg/kg BW exhibited significant antipyretic activity (p < 0.05). The ethanolic extract from beligo fruit flesh possesses antipyretic activity in induced Wistar rats, suggesting its potential use as a fever-reducing medication. Keywords: Antipyretic; Benincasa hispida (Thunb.) Cogn; fever